"LEARN"ing what is important to children and young people with intellectual disabilities when they are in hospital. Issue 5 (16th January 2018) - Oulton, K.; Sell, D.; Gibson, F.
Abstract : Background: The need to review health service provision for children and young people (CYP) with disabilities and their families in the United Kingdom has been expressed in multiple reports: the most consistent message being that services need to be tailored to meet their individual needs. Our aim was to understand the hospital‐related needs and experiences of CYP with intellectual disabilities. Method: An ethnographic study of a neurosciences ward and outpatient department was conducted within a paediatric tertiary hospital setting. Results: Five themes, developed using the acronym LEARN, explained what is important to CYP with intellectual disabilities in hospital: (i) little things make the biggest difference, (ii) eliminate unnecessary waiting, (iii) avoid boredom, (iv) routine and home comforts are key and (v) never assume. Conclusions: It is imperative that the present authors continue to challenge the idea that it is acceptable to exclude CYP with intellectual disabilities from research because of their inability to participate.